Genetic Characterization of Ganoderma Sp. UsingInterfertility and Molecular Methods - Hussin, Husrita (2009)
Laccate polypores of the genus Ganoderma are wide spread but species identification cannot be easily done based only on traditional methods. The species of Ganoderma boninense is of economic importance to Malaysia as it causes the disease Basal Stem Rot (BSR) of oil palms. In this study, 53 Ganoderma were isolates from different hosts. Which are 23 isolates from infected oil palms (Elaeis guineensis), 12 from various non-Elaeis palmae hosts, 18 Ganoderma from non-palm woody hosts and 2 non-Ganoderma as an outgroup specimens were used to conduct interfertility studies, Random Amplified Microsatellite DNA (RAMS) and Internal Transcribe Spacer (ITS1). The interfertility studies showed that 34 laccate Ganoderma that collected from various palmae hosts determined as G. boninense whereas another 12 laccate Ganoderma samples and all 7 non-laccate Ganoderma specimens were non boninense. The compatible dikaryotic pairs were further validated through sporophore induction studies of which all those tested as G. boninense produced viable fruiting bodies. Molecular studies using Random Amplified Microsatellite (RAMS) generated a dendrogram of two major clusters. Cluster I, all the laccate, non-laccate Ganoderma and two non-Ganoderma samples which are determined as non-boninense G. by interfertility study were grouped together except two isolates which is determined as G. boninense (FA3026 and FA5014). This showed that RAMS not totally support interfertility studies. Clusters II consists of all laccate Ganoderma which are determined as G. boninense in interfertility study. The dendrogram constructed from gene sequence data of ITS 1 region of the rDNA produced three major clusters. Major Cluster I consisted of outgroups samples PLP, while Major Cluster II was WRR. Major Cluster III separated into two sub-cluster IIIA and IIIB, sub-cluster IIIA were consisted of all laccate Ganoderma samples and this sub-cluster were separated into two, 34 samples are determined as G. boninense and 12 samples are non-boninense G. Sub-cluster IIIB consisted of 7 non-laccate Ganoderma and determined as non-boninense G. BLAST analysis showed that all 34 determined as G. boninense, 4 were G. neojaponicum, 2 isolates were G. formosanum, 3 were G. lucidum, 2 G. tsugae, 2 G. resinaceum, 2 G. cupreum, 3 G. adspersum and 4 isolates as a G. australe. This investigation found that ITS not only analysed at genus level but also able to identified at species level. The phylogenetic analysis by ITS regions showed agreement with the interfertility data but not with RAMS analysis. The clustering of Ganoderma isolates in ITS and RAMS are difference because different approaches were use. With a different types of primers used in the two different DNA-based methods, the banding sites in fungal genome would also be different which could lead to different clustering of the isolates in the cluster analysis. In this study found that G. boninense is a single species which causes the basal stem rot disease on oil palm in Malaysia. G. boninense also can effect to non-palmae woody host, which found on Caesalpinia sappan.